Children and Pesticides - Frederick M. Fishel (EDIS)
Children act fast, but so do poisons, including pesticides. Fortunately for most parents, their children are not harmed when the parents have a momentary lapse and aren’t supervising them for a short time. But how would parents respond if they suddenly turn around, and their toddler is holding a can of household aerosol insect killer? This 3-page fact sheet outlines some facts and precautionary measures regarding children and pesticides in the home environment, so parents have a better idea of how to keep harmful chemical products away from their children. Written by F.M. Fishel, and published by the UF Department of Agronomy, March 2013.